Pengaruh Faktor Good Corporate Governance, Free Cash Flow, dan Leverage Terhadap Manajemen Laba - Dian Agustia (Jurnal Akuntansi dan Keuangan, 2013)
The aim of this research is to provide empirical evidence on the impact of good corporate governance, free cash flow, and leverage ratio on earnings management. Good corporate governance is measured by audit committee’s size, the proportion of independent commissioners, institutional ownership, and managerial ownership. Discretionary accrual is the proxy of earning management. This research used 14 textile companies listed in Indonesia Stock Exchange, selected using purposive sampling method, during the research period 2007-2011. Data were analyzed using multiple regression method. Based on the result of analysis concluded that all components of good corporate governance (audit committee’s size, the proportion of independent commissioners, institutional ownership, and managerial ownership), have no significant effect on earnings management, while leverage ratio has a significant effect on earnings management, and free cash flow has a negative and significant effect on earnings management. It means that companies with high free cash flow will restrict the practice of earnings management.